Oral health and dental morbidity in long‐term allogeneic blood and marrow transplant survivors in Australia. (26th July 2018) - Dyer, G; Brice, L; Schifter, M; Gilroy, N; Kabir, M; Hertzberg, M; Greenwood, M; Larsen, SR; Moore, J; Gottlieb, D; Huang, G; Hogg, M; et al.
Abstract: Background: Oral and dental disease is a major cause of long‐term morbidity following allogeneic blood and marrow transplantation (Allo‐BMT). This study aimed to describe the extent and range of oral and dental complications in BMT recipients and to identify gaps in service provision provided to this high‐risk group. Methods: Participants were Allo‐BMT recipients, aged >18 years, and received transplants between 2000 and 2012 in NSW. They completed seven surveys, the purpose‐designed Sydney Post‐BMT Study survey and six other validated instruments. Results: Of 441 respondents, many reported dry mouth (45.1%), dental caries (36.7%), mouth ulcers (35.3%), oral GVHD (35.1%), gingivitis (16.2%), tooth abscess (6.1%) and oral cancer (1.5%). Regular dental visits were reported by 66.2% of survivors. Middle–high income, older age and geographic location showed a positive association with regular dental visits. Of those who did not visit the dentist regularly, 37% stated they did not feel it necessary, 36% reported cost and 20% stated it was not advised by the treating team. Conclusion: Despite oral complications commonly occurring after Allo‐BMT, many survivors receive inadequate dental care. These results emphasize the need for improved oral health education, the importance of regular dental checks and improvement in the delivery of dental health services for BMT survivors.